GLP-1 receptor agonists and cardiovascular outcome trials: An update - Eirini Andrikou; Costas Tsioufis; Ioannis Andrikou; Ioannis Leontsinis; Dimitrios Tousoulis; Nikolaos Papanas (Hellenic Journal of Cardiology, 2019)
Major cardiovascular (CV) outcome trials with glucagon-like peptide-1 receptor agonists (GLP-1 RAs) are currently available. These agonists have proven their CV safety, in harmony with the US Food and Drug Administration (FDA) recommendation for antidiabetic drugs. The potential cardioprotective effect of incretin-based therapies is attributed to their multiple non-glycaemic actions in the CV system, including changes in insulin resistance, weight loss, reduction in blood pressure, improved lipid profile and direct effects on the heart and vascular endothelium. Liraglutide, semaglutide and albiglutide have been demonstrated to reduce the risk of major adverse cardiac events (MACE), whereas lixisenatide and extended-release exenatide had a neutral effect. Thus, it is conceivable that there are different drug-specific properties across the class of GLP-1 RAs. In this review, we discuss the results of the five recently published randomised CV outcome trials with GLP-1 RAs, along with the potential differences and the pleiotropic actions of these agents on the CV system. Keywords: Cardiovascular disease, Diabetes mellitus, Randomised controlled trials, Treatment